Exogenous Application of GABA Improves PEG-Induced Drought Tolerance Positively Associated with GABA-Shunt, Polyamines, and Proline Metabolism in White Clover - Yong, Bin; Xie, Huan; Li, Zhou; Li, Ya-Ping; Zhang, Yan; Nie, Gang; Zhang, Xin-Quan; Ma, Xiao; Huang, Lin-Kai; Yan, Yan-Hong; Peng, Yan (Frontiers in Physiology, 2017)
In order to investigate the physiological effects of exogenousγ-aminobutyric acid (GABA) on drought tolerance in white clover (Trifolium repens), GABA shunt, polyamines (PAs), and proline (Pro) metabolism were examined after plants pretreated with or without GABA (8 mM) and then exposed to water or 15% PEG-induced drought stress in growth chamber. In this study, exogenous application of GABA effectively alleviated drought-induced damage in leaves, as reflected by significantly higher relative water content, lower electrolyte leakage, lipid peroxidation, and leaf wilt. Exogenous GABA further promoted drought-induced increases in GABA transaminase and alpha ketone glutarate dehydrogenase activities, but inhibited glutamate decarboxylase activity under both control and drought conditions, resulting in an increase in endogenous glutamate (Glu) and GABA content. Besides, exogenous GABA could well accelerated PAs synthesis and suppressed PAs catabolism, which lead to the extremely enhanced different types of PAs content (free Put and Spd, insoluble bound Spd and Spm, soluble conjugated Spd and Spm, and total Put, Spd and Spm) under drought stress. In addition, exogenous GABA application further activated drought-induced Δ1-pyrroline-5-carboxylate synthetase and proline dehydrogenase activities, but suppressed drought-facilitated ornithine -δ- amino transferase activities, leading to a higher Pro accumulation and metabolism in GABA-pretreated plants in the middle and last period of drought. The results suggested that increased endogenous GABA by exogenous GABA treatment could improve drought tolerance of white clover associated with a positive regulation in the GABA-shunt, PAs and Pro metabolism.